Kaliṅkattupparaṇiyārāycci - Irākavaiyaṅkār, Mu., 1878-1960 (SAMP early 20th-century Indian books project ;, 1925)
Study of Kaliṅkattup paraṇi, poem on Kulottunga I, fl. 1070-1118, Chola King, by Cayaṅkoṇṭār.